Quality of life, aging and physical activity Qualidade de vida, envelhecimento e atividade física - Mazo G.Z.* (2007)
The objective of this paper is to discuss the themes of quality of life (QL), aging and physical activity (PA) from a theoretical perspective, an ageing population will be a part of our daily life in the near future. Faced with this prospect, we must seek to guarantee the rights of the elderly, ensuring that they have acceptable living conditions and QL. In this context PA is a means of achieving active aging, promoting the health of seniors and, as a consequence, improving their QL. There is an increasing amount of research being carried out on this subject, but, even so, further studies are needed into the relationship between PA and QL in the elderly, with clear conceptual definitions of PA and QL, with larger sample sizes, better control of variables and the use of PA and QL measurements that have passed due psychometric testing. Investigations of the subject will aid proposals for effective interventions, aimed at active and healthy aging with quality of life.